Spór o Borowskiego - Krupa, Bartłomiej (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2018)
The polemic at the turn of 1947 caused by Tadeusz Borowski’s pamphlet Alicja w krainie czarów [Alice in Wonderland] (Pokolenie 1947, nr 1) raised the portcullis to the annals of Polish post-war prose. To the defence of Zofia Kossak-Szczucka, author of Z otchłani [Out of the Abyss], took arms several literary critics of Catholic provenance while in turn their shields did raise for the neophyte writer, well known pens from literary periodicals such as Kuźnica or Odrodzenie. Soon however, the exchange of blows reached beyond the very issue of diction in writing on concentration camps or indeed, Marxist-Catholic wars waged across ideology. The cause itself raised questions on the very nature of prose. More so, lines were drawn across its literary essence (obligation and tasks of literature), theoretical nature (status of the narrator and their obligations towards the author), historical role (social attitudes during World War II and the period of Stalinism) and finally, the moral question (nihilism and the ethical responsibility of the creative artist). This author therefore discusses respectively three stages of The Polemic Over Borowski; the 1940s, the 1970s and discussion that has arisen since the 1980s. This literary chronology testifies to the “long extent” of the debate and its continued relevance, proof of the everlasting endurance of national myths, which the neophyte writer was to question in the yester beginnings of modern Polish prose.
The Polemic Over Borowski
Keywords: Tadeusz Borowski; polemika krytycznoliteracka